Extinction debt of cities and ways to minimise their realisation: a focus on Melbourne. (May 2014) - Hahs, Amy K.; McDonnell, Mark J.
<x xml:space="preserve">Abstract</x> The formation and growth of cities sets in train a slow process of local species extinction, although it can take a long time for that extinction to be realised. Using Melbourne as an example, the authors ask 'What plant species are potentially at risk and what strategies and actions could minimise the predicted negative outcomes?'